Reaching new wheat varieties to farmers: Experiences from outreach activities in western Uttar Pradesh region of India - Singh, Sanjay Kumar; Singh, Gyanendra; Tyagi, Bhudeva Singh; Tiwari, Vinod; Sharma, Indu (Journal of Cereal Research, 2014)
The productivity of wheat at farmerâ€™s field in western UP is comparatively low and needs efforts for awareness to increase area under newly released cultivars to create a varietal mosaic for defense against airborne pathogens, and seed production. For this, a strategy was devised involving research institutes, SAUs, seed growers and innovative farmers. The varietal cafeteria of a dozen wheat varieties was demonstrated in western UP for comparison with the existing varieties. The farmers were provided seed of newly released variety DBW 71 so as to get their opinion, multiplication of seed at village level and its popularisation as a high yielding, disease resistant with better quality cultivar in districts of western UP. The yields of DBW 71 at farmerâ€™s field ranged from 3.6-7.1 t/ha depending upon the sowing time and production technologies adopted. The feedback was very encouraging and this approach can be replicated in other parts of the country. Â